A novel dynamic vibration absorber for vibration control of piping systems under multi-frequency harmonic excitations - Lihang Yin; Wei Xu; Zechao Hu; Liantao Xiao (Scientific Reports)
Abstract To suppress the significant vibration line spectra of piping systems under multi-frequency harmonic excitations, a novel dynamic vibration absorber (NDVA) is designed. The NDVA integrates numerous independent resonant units within a finite space through an ingenious structural design and possesses rich frequency regulation characteristics. A vibration model of the piping system equipped with the NDVA is established, and the approximate equivalent parameters of both the piping and the resonant units are inverted based on the frequency response function (FRF) test results. These parameters can be substituted into the model to enhance the accuracy and validity of the theoretical calculations. Based on the relationship between the absorbing bandwidth of the NDVA and the intervals of multi-frequency excitation frequencies, a tailored regulation strategy for different densities of excitation frequencies is proposed. Subsequently, the multi-frequency vibration reduction capability of the NDVA is verified through an example involving dual-frequency harmonic excitations. When there is a notable difference in the intensities of the multi-frequency vibration line spectra, a genetic algorithm is utilized to optimize the mass allocation of the resonant units. Simulation and test results demonstrate that the maximum response amplitude of the optimized system is further reduced.